The Effect of Cost Reduction as Part of Supply Chain Drivers’ Element and Customer Satisfaction on Purchasing and Logistics Performance - Dwi Anna Kristanti; Novelia Asita Mranani (Master of Management, School of Business and Management, Petra Christian University, 2024)
Dynamic capabilities became a manufacturing industry benchmark for surviving and adapting to the dynamic environment change, including the COVID-19 pandemic. In a manufacturing company, supply chain management performance becomes the main activity that must be effective and efficient. Two supply chain drivers were observed in this study to perform optimal supply chain management, namely cost reduction and customer satisfaction, which became the company's drivers in establishing partnerships in purchasing and logistics, affecting the company's purchasing and logistics performance. This study investigated the effect of cost reduction and customer satisfaction on the partnerships in purchasing and logistics and purchasing and logistics performance. This study used a descriptive quantitative approach. The population comprised operational managers of food and beverage production in Indonesia, with 711 people. The sampling used a random sampling technique, and 50 respondents’ data was obtained. The data collection was performed by distributing online questionnaires. Data processing was performed with the Partial Least Square (PLS) method. The result found that cost reduction and customer satisfaction affect partnerships in purchasing and logistics, customer satisfaction and partnerships in purchasing and logistics affect purchasing and logistics performance, and cost reduction does not affect purchasing and logistics performance. Theoretical contribution of research to add enrichment to the resource-based view theory on competitiveness with supply chain performance.